Deflection Mechanism and Safety Analysis of Coal Mine Shaft in Deep Soil Strata. (5th December 2019) - Han, Jihuan; Zou, Jiuqun; Hu, Chenchen; Yang, Weihao
Abstract : The main shaft and auxiliary shaft in the Guotun Coal Mine underwent large deflections, with deflection values of 359 mm and 322 mm, respectively. These two deflections represent the first occurrence of such large vertical shaft deviations in the soil strata in China. The deflection problem has seriously affected the hoisting safety and lining safety and has become a serious impediment to the sustainable production of mines. Therefore, the deflection mechanism must be determined. For this purpose, based on mining subsidence theory, the spatial probability integral method and a more accurate time function were used to establish a model, called 3D dynamic prediction model, for predicting the shaft movement. The formulas for calculating the lining stress caused by coal mining were based on established models. With measured shaft deflection data, the prediction parameters for deep soil strata were calculated on the basis of an inversion analysis. A comparative analysis of measured and calculated deflection values revealed that the reason for shaft deflection in Guotun Coal Mine is the insufficient size of the protection coal pillar (PCP); namely, the design parameters of the PCP in current codes are not applicable to the deep soil strata. As a result, under the asymmetric mining conditions, mining causes the shaft to deflect without damage and under the symmetric mining conditions, mining causes the lining to fracture. The results have an extremely important significance for the prevention and control of shaft deflection, for the rational design of PCP, and for the sustainability of mine production.